1969
DOI: 10.1007/bf02541216
|View full text |Cite
|
Sign up to set email alerts
|

Identification of some acids from autoxidation of methyl linoleate

Abstract: The acids from autoxidation of methyl linoleate have been analyzed as their methyl esters by combined capillary gas chromatography‐mass spectrometry (GC‐MS). The principal components were hexanoic, trans‐2‐octenoic, suberic and azelaic acid. Minor components included formic, pentanoic, heptanoic, trans‐2‐heptenoic, octanoic and nonanoic acid. In addition,trans‐2,3‐epoxy‐octanoic acid was isolated as its methyl ester by preparative GLC and was identified by means of NMR, high resolution MS, IR and by conversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1971
1971
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…They are, however, produced during the autoxidation of higher fatty acids and their glyceride esters. For instance, Horvat et al (1969) identified 12 fatty acids, including Cl and C5-C9, from autoxidation of methyl linoleate at room temperature. Several reaction pathways have been proposed to explain the formation of short-chain fatty acids.…”
Section: Acidsmentioning
confidence: 99%
“…They are, however, produced during the autoxidation of higher fatty acids and their glyceride esters. For instance, Horvat et al (1969) identified 12 fatty acids, including Cl and C5-C9, from autoxidation of methyl linoleate at room temperature. Several reaction pathways have been proposed to explain the formation of short-chain fatty acids.…”
Section: Acidsmentioning
confidence: 99%
“…The pentanoic acid, hexanoic acid, and octanoic acids were produced by the oxidation of methyl linoleic acid [ 32 ] and with a higher concentration in SD-raisins, fresh grapes, and AD-raisins, respectively. Dodecanoic acid and 2-ethyl hexanoic acid were only identified in PAD-raisins with a concentration of more than ten µg/g ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The descriptions, precursors of identified compounds [11,12,[21][22][23][24], and aroma descriptors [20,[25][26][27] are presented in Table 2. The fruity, green and sweet aromas [25,26] producing compounds such as decanal, 1-hexanol, 3-octen-2-one and 2-pentyl furan were the leading compounds in terms of concentration, and their contents decreased with storage time.…”
Section: Discussionmentioning
confidence: 99%
“…In sun-dried raisin, all acidic compounds octanoic acid, heptanoic acid, pentanoic acid, and hexanoic acid showed higher concentrations when specifically stored for 8 and 12 months, but in air-dried raisin, these showed irregular trends during storage. The acid compounds were derived from the autoxidation of methyl linoleic acid [24]. Some volatile compounds are specific to the drying method, such as 2-nonanol and methyl octanoate, which were only present in air-dried and sun-dried raisins, respectively.…”
Section: Discussionmentioning
confidence: 99%